IoT high-frequency electronic transformer with dimmable output voltage using PWM signals - Trillos-León, Nelson; Barrero-Pérez, Jaime; Jaimes-Flórez, Julian; Rojas, David (Informador Técnico, 2021)
This work presents the design, simulation, and implementation of a low-power electronic transformer, which output effective voltage can be controlled wirelessly through WIFI, via a user interface on a mobile phone. The methodology used in this project consists of 4 stages, a rectifier, an inverter, the inverter’s control system, and a ferrite reducer. The inverter has a full-bridge design and was implemented using MOSFET. The control system can vary the frequency and duty cycle of the output signals, by phase shifting the control signals, thus achieving the functionality of reducing the effective output voltage. Circuit design simulations were performed using PsPice Orcad. The implementation and the mathematical model of the built electronic transformer are carried out. The designed transformer operates with a maximum input voltage of 120 Vrms at 60 Hz at frequencies between 20 kHz and 30 kHz, which are controlled through the user interface; can reduce a 120 Vrms 60 Hz input signal to an effective voltage between 10 Vrms and 20 Vrms at a maximum power of 50 W. This project presents the feasibility of developing electronic transformers with variable output voltage, remotely controlled using IoT technology.